Integral Identity Method to Fluid Flow through Cracked Porous Media with Different Wetting Abilities (International Journal of Innovative Research in Computer Science & Technology, 2022)
It is a notable actual peculiarities when a  permeable media is totally immersed with a non-wetting  liquid. For instance, water is brought into contact. The last  option will more often than not precipitously stream into  the medium, dislodging the non-wetting liquid. In this  paper, we utilize indispensable personalities with  intersecting hyper-mathematical series to address the  progression of two immiscible fluids in a broke permeable  medium. The methodology adopted for the solution is  followed by transform of non-linear differential system  into an ordinary differential equation. Subsequently  obtained equation is convert into diffusion equation by  applying similarity variable by standard transformation  and further transfer into the confluent hyper geometric  equation. The acquired arrangement as far as intersecting  hyper mathematical series give an articulation for wetting  stage immersion. The outcomes exhibit the straightforward  examination to acquire a scientific arrangement of the non direct differential condition of imbibitions peculiarity  under extraordinary condition in a broke permeable media  wherein the water infiltrating the crease along the broke is  sucked into the squares of rock under the activity of  hairlike powers and how much water entering the square  in the rudimentary volumE
Keywords: Capillary Forces; Confluent Hyper Geometric Series; Cracked Porous Media; Diffusion Equation; Imbibitions Phenomeno; Non-linear Differential Equation